Fischerei auf Ostsee-Steinbutt nach der Laichzeit nicht mehr rentabel - Mohr, H. (1989)
Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010